Education Needs of Families of Transgender Young People: A Narrative Review of International Literature. (2nd January 2018) - Sharek, Danika; Huntley-Moore, Sylvia; McCann, Edward
ABSTRACT: Education plays a crucial role in the lives of families of transgender young people and mental healthcare practitioners are well-placed to support families in this regard. This paper reports findings from a narrative review of 31 papers that explored the education needs of families of transgender young people. The emergent themes were synthesised to develop a five-stage model that depicts the role of education in the lives of these families. Key themes included: (i) learning that a family member is trans; (ii) family responses; (iii) accessing education and information; (iv) impact on the individual; and (iv) moving beyond the individual. The key implications for mental health practitioners, families, and future research are discussed.